Air–sea interactions amplified by tropical cyclones break the South China Sea summer monsoon - Minghao Bi; Ke Xu; Riyu Lu (npj Climate and Atmospheric Science)
Abstract Summer monsoon breaks can have far-reaching impacts by triggering abnormal weather both locally and remotely. However, their formation mechanisms remain incompletely understood, with intraseasonal oscillations (ISOs) widely recognized as a primary driver. This study investigates South China Sea monsoon break events and finds that 72.9% originate from the Philippine Sea, associated with ISOs, while the residual 27.1% are locally generated, which have yet to be elucidated previously. Our results suggest that these locally generated events are often preceded by anomalously active tropical cyclones, which amplify in situ air–sea interaction, inducing SST cooling that increases large-scale atmospheric stability, thereby promoting monsoon break establishment. Moreover, differing from ISO-related monsoon breaks that increase precipitation over the Yangtze River Valley, locally generated breaks induce significant warming over South China. The diverse mechanisms and climate impacts of monsoon breaks revealed in this study may provide new insights for further improvement of subseasonal predictions.